Method for growing large-size titanium-doped sapphire crystal by kyropoulos method

Large-size titanium-doped sapphire crystals were grown by bubble-dripping method, and the thermal field and Ar/CO mixed gas protection were constructed using high-purity graphite materials, which solved the problems of Ti3+ ion doping stability and uniformity in the growth of titanium-doped sapphire crystals, and achieved the High-quality, low-defect large-size crystal growth meets the needs of high-end lasers.

CN119121383AActive Publication Date: 2024-12-13TDG HLDG CO LTD +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411621998.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2024-12-13
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

The prior art is difficult to grow high-quality, low-defect, and good uniform titanium doped sapphire crystals with large diameters (>200mm), especially in controlling the stable existence and uniform distribution of Ti3+ ion doping.

Method used

The method of growing large-size titanium-doped sapphire crystals by bubble growth is used to build a heat field through high-purity graphite materials to reduce heat field pollution. The mixed gas of Ar and CO is used as a protective gas to suppress adverse reactions in the furnace, and the double heating body is used to accurately control it. Temperature distribution reduces stress concentration and achieves the growth of large-size, high-quality, and low-defect crystals.

Benefits of technology

Grow large-size titanium doped sapphire crystals with a diameter of 300-353mm and a weight of 100-145kg, which improves the crystallinity and uniformity of the crystals, reduces defects, enhances the application value in the laser field, and improves the crystal growth temperature field environment. and doping concentration control.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121383A_ABST
    Figure CN119121383A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of crystal growth, and particularly relates to a method for growing a large-size titanium-doped sapphire crystal by a kyropoulos method, which comprises the steps of raw material preparation and filling, heating and melting, temperature regulation and seeding, crystal growth, crystal cooling in-situ annealing and wafer H2 annealing. A high-purity graphite material is adopted to construct a thermal field, thermal field pollution is reduced, temperature distribution is accurately controlled through double heating bodies, and a stable temperature gradient field is formed; raising the temperature, introducing mixed gas of Ar and CO as protective gas, inhibiting adverse reaction in the furnace, and maintaining stable existence of Ti < 3 + > ions in the molten liquid; in the Kyropoulos method crystal growth process, contact with a crucible is avoided, stress concentration is reduced, crystal uniformity is improved, the efficient growth method of the large-size, high-quality and low-defect titanium-doped sapphire crystal is achieved, and the manufacturing requirements of high-end lasers and optical devices are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of crystal growth, and in particular relates to a method for growing large-size titanium-doped sapphire crystals by a kyberyzing method. Background Art

[0002] Titanium-doped sapphire crystals (Titanium sapphire crystals) are mainly used in the field of laser technology. They are the most widely used tunable laser solid materials with excellent laser properties, such as wide emission bandwidth, excellent thermal, optical, physical, chemical and mechanical properties. With the rapid development of the laser industry, the demand for all-solid-state lasers continues to rise. All-solid-state lasers made of titanium-doped sapphire have the characteristics of simple structure, easy use, high power, wide tuning range, high working efficiency, high reliability and long service life. They are widely used in laser spectroscopy, nonlinear optics, lithography technology, atmospheric monitoring, laser medical treatment and scientific research. At present, there are three main technical difficulties in the manufacture of large-size titanium-doped sapphire crystals internationally: ① It is difficult to grow large-diameter crystals (diameter greater than 200mm); ② It is difficult to control the growth of high-doping concentration and low-defect crystals; ③ Ti in a large diameter range 3+ The uniform distribution of concentration is difficult to control.

[0003] The main methods for growing large-sized Ti-doped sapphire crystals include the Czochralski method, heat exchange method, guided mold method, temperature gradient method, and kyberyzing method. The advantage of using the kyberyzing method to grow large-sized Ti-doped sapphire is that it can achieve precise control of the thermal field, crystal growth atmosphere, growth gradient, etc., and produce large-diameter (>200mm) crystals. However, due to the doping of Ti 3+ The ionic radius is 0.076nm, which is smaller than that of Al2O3 matrix. 3+ (0.053nm) ion radius is 43% larger. In the process of growing large-sized Ti-doped sapphire crystals, Ti 3+ Ion doping has a strong segregation phenomenon, so the technical difficulty of growing large-sized high-quality titanium-doped sapphire crystals using the kybery process is that the uniformity of doping and the Ti content need to be controlled during the growth process. 3+ The stable existence of ions.

[0004] The invention patent with publication number CN104357904B discloses a method for growing titanium sapphire crystals with a cladding layer by placing a seed crystal at the center of the bottom of the crucible and controlling the temperature of the seed crystal and the power of the heater at the bottom of the crucible. The method can achieve high-quality large-size titanium sapphire crystals with a diameter of 200-250 mm, but is prone to thermal field pollution and unstable thermal field insulation performance, which will directly affect the single crystallinity and uniformity of the crystal and is not suitable for growing crystals with a diameter greater than 300 mm. The invention patent with publication number CN111074337B discloses a method and device for growing high-concentration titanium-doped sapphire crystals by a guided mold method. The guided mold method can shape the growth by designing the mold shape. Although the titanium doping concentration is increased, it is difficult to control the crystal growth if a large-size crystal is grown, and high-quality crystals cannot be grown.

[0005] Therefore, it is necessary to study a method for growing large-sized Ti:sapphire crystals using the Kyropoulos method to ensure low defects, single crystallinity and uniformity of the crystals. Summary of the invention

[0006] In view of the technical shortcomings of the existing kyropoiesis method for growing large-sized titanium-doped sapphire crystals, the present invention provides a method for growing large-sized titanium-doped sapphire crystals by kyropoiesis, which includes the steps of raw material preparation and loading, heating the melt, temperature-adjusting seeding, crystal growth, crystal cooling in-situ annealing, and wafer H2 annealing. The present invention uses high-purity graphite materials to construct a thermal field to reduce thermal field pollution, and accurately controls the temperature distribution through a double heating body to form a stable temperature gradient field; a mixed gas of Ar and CO is introduced as a protective gas during heating to inhibit adverse reactions in the furnace and maintain the Ti content in the melt. 3+ The stable existence of ions; in the process of growing crystals by the kyberysis method, there is no contact with the crucible, which reduces stress concentration, improves crystal uniformity, and realizes the efficient growth of large-size, high-quality, low-defect doped titanium sapphire crystals to meet the manufacturing needs of high-end lasers and optical devices.

[0007] The present invention provides a method for growing large-size titanium-doped sapphire crystals by a kyberysis method. The heat preservation structure of the heat field for crystal growth is composed of a bottom heat preservation plate, an annular heat preservation cylinder and an upper heat preservation plate, and a carbon felt material with a graphite coating is adopted. The heating structure is composed of a side main heater and a bottom auxiliary heater, and a graphite material is adopted. The crystal growth method comprises the following steps: 1) Raw material preparation and filling: Titanium dioxide powder and alumina powder are mixed evenly, wherein the mass percentage of titanium dioxide mixed is 0.2-0.6%, and then roasted to obtain titanium-doped alumina sintered ingots, which are crushed and then filled; 2) Heating the melt: A mixed gas of Ar and CO is introduced as a protective gas, wherein the volume fraction of CO is 4.5-7.0% and the rest is Ar, and the temperature is raised to melt the raw materials; 3) Temperature adjustment for seeding: After the raw materials are fully melted, wait for the temperature to continue to rise until it is 10-18°C higher than the full melting temperature of the raw materials. At this time, the melt is overheated and strong convection occurs. Then reduce the heating power to make the melt surface temperature 2048-2053°C, and the descending seed crystal contacts the liquid surface for melting and begins crystal growth; 4) Crystal growth: Control the crystal growth rate to 0.2-0.5 mm / h. When the crystal grows to the required size, pull it out of the melt; 5) Crystal cooling in-situ annealing: Increase the CO concentration in the mixed gas, where the CO volume fraction is 9.5-14.5%, and perform cooling annealing at the same time. After the temperature in the furnace drops to room temperature, take out the crystal, and the crystal diameter is 300-350mm; 6) Wafer H2 annealing: The cut wafer is subjected to high temperature H2 annealing.

[0008] Among them, the density of carbon felt material is ≥0.15g / cm 3 , the surface graphite coating roughness ≤ 0.1μm, coating thickness ≥ 2mm.

[0009] Among them, the inner diameter of the annular insulation cylinder is 120-200mm larger than the outer diameter of the crucible.

[0010] Among them, the graphite heater is in the shape of an "S" disk.

[0011] Wherein, in step 1, the mass percentage of titanium dioxide is 0.3-0.5%, the purity of titanium dioxide powder is ≥99.95%, and the purity of aluminum oxide powder is ≥99.995%.

[0012] Preferably, in step 1, the mass percentage of titanium dioxide is 0.35-0.45%.

[0013] Among them, in step 1, a mixer is used to evenly mix titanium dioxide powder and alumina powder, the mixture is mixed for more than 24 hours, and then loaded into a cylindrical mold for isostatic pressing. After that, a titanium-doped alumina sintered ingot is obtained by roasting, and then it is crushed into two specifications of block material and fine material, and filled into a molybdenum crucible.

[0014] Preferably, in step 1, the calcination temperature is 1750-1900° C. and maintained for 5-15 hours. The calcination is to make the raw materials mixed and doped more uniformly through solid phase diffusion reaction.

[0015] Preferably, in step 2, in the mixed gas of Ar and CO, the volume fraction of CO is 5%-6.5%, preferably 5.5% or 6%, and the gas flow rate is 5-8 L / min, preferably 6 L / min or 7 L / min.

[0016] Preferably, in step 2, the heating rate is 40-68°C / h, and the reaction time is 30-55h.

[0017] Preferably, in step 3, the seed crystal is a sapphire seed crystal or a titanium-doped sapphire seed crystal.

[0018] Preferably, in step 3, after the raw materials are fully melted, the temperature is allowed to continue to rise until it is 12-16°C higher than the fully melted temperature of the raw materials. At this time, the melt is overheated and strong convection occurs, so that the raw materials form a uniformly distributed melt. The heating power is then reduced. When the melt surface temperature is 2051.8-2052.8°C, the seed crystal is lowered to contact the liquid surface for melting and cleaning of impurities and polycrystalline on the lower end surface of the seed crystal. The heating power is then reduced. When the melt surface temperature reaches 2048.2-2050.2°C, crystal growth begins.

[0019] Preferably, in step 4, the crystal growth rate is 0.25-0.45 mm / h, more preferably 0.3-0.4 mm / h.

[0020] Preferably, in step 5, the CO concentration in the mixed gas is increased, wherein the CO volume fraction is 10.0-12.0%, preferably 10.5%, 11% or 11.5%, increasing the reducing atmosphere in the furnace, which can effectively inhibit Ti 3+ The ions are oxidized to Ti 4+ ions, improving crystal uniformity.

[0021] Preferably, in step 5, the temperature reduction annealing treatment is performed at a rate of 11.2-16.2°C / h, preferably 12°C / h, 13°C / h, 14°C / h, 15°C / h or 16°C / h.

[0022] Preferably, in step 6, the cut wafer is subjected to high temperature H2 annealing, the heating rate is 55-185°C / h, the annealing temperature is 1800-1900°C, the holding time is 10-50h, and the cooling rate is 45-135°C / h.

[0023] Preferably, in step 6, the cut wafer is subjected to high temperature H2 annealing, the heating rate is 75-155°C / h, the annealing temperature is 1820-1860°C, the holding time is 20-40h, and the cooling rate is 55-115°C / h to promote Ti 4+ ions are reduced to Ti 3+ ions, increasing Ti 3+ The proportion of ions increases the crystal quality factor, that is, the quality factor value.

[0024] The beneficial effects of the present invention are: (1) Produce large-sized high-quality titanium-doped sapphire crystals: grow large-sized titanium-doped sapphire crystals with a weight of 100-145kg, a diameter of 300-353mm, and a height of 350-450mm. The crystallinity is high, and combined with high-temperature hydrogen annealing process, the Ti 4+Reduction to Ti 3+ Ions, while high temperature annealing will effectively improve crystal uniformity, reduce crystal defects, avoid uniformity problems affecting its application in lasers and other fields, the quality factor value is greater than 150, thereby improving its application value in lasers and other fields; (2) Improve the crystal growth temperature field environment: When using the kyberyzing method to grow large-sized titanium-doped sapphire crystals, the thermal field requires extremely high stability. The "all-carbon" graphite thermal field is designed. The thermal field does not deform, has low cost, and has good thermal insulation performance. It avoids abnormal temperature gradients and solid-liquid interface instability caused by thermal field deformation, and solves the problems of easy deformation of traditional metal thermal fields and volatile pollution of metal-zirconia thermal fields. Dual graphite heaters (side main heater and bottom auxiliary heater) are independently controlled to replace the single heating element structure of the traditional kyberyzing method. Through the cooperation of the dual heaters, the temperature field and melt flow field in the crystal growth furnace are regulated to maintain the small temperature gradient and "micro-convex" solid-liquid interface stability required for the growth of titanium-doped sapphire crystals. (3) Precisely control the gas ratio: During the crystal growth process, a mixed atmosphere of Ar and CO is used to replace the traditional vacuum crystal growth or single Ar protective atmosphere crystal growth process technology. The present invention reduces the contamination of the melt and crystal by the volatilization of carbon at high temperature by adjusting the parameters of the mixed atmosphere components, and effectively controls the growth rate and quality of the crystal. On the other hand, the weakly reducing mixed atmosphere of Ar and CO in the furnace can also effectively inhibit the Ti 3+ The ions are oxidized to Ti 4+ ion; (4) Higher doping concentration: By strictly controlling the doping ratio of titanium ions at 0.2-0.6%, the doping uniformity and purity of the raw material preparation process are controlled. After the raw materials are fully melted, the liquid surface temperature rises, causing the melt to overheat and produce strong convection, which can improve the doping and mixing uniformity of the melt at high temperature; using a graphite thermal field combined with the kypermethrin method to grow crystals, a stable temperature environment is provided, and Ti in the melt is 3+ The segregation phenomenon of ion doping is weakened, ensuring the stable growth of crystals at high doping concentrations; In general, compared with the prior art, the present invention not only improves the performance and quality of large-sized titanium-doped sapphire crystals, but also improves the controllability and stability of the preparation process thereof, and has significant advantages. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a process flow chart for growing large-size Ti-doped sapphire crystals; Figure 2 This is a simplified diagram of the structure of the crystal growth thermal field; Among them, 1 is the upper insulation board, 2 is the annular insulation tube, 3 is the bottom insulation board, 4 is the side main heater, and 5 is the bottom auxiliary heater. DETAILED DESCRIPTION

[0026] The present invention is further described in detail below in conjunction with specific implementation methods to better reflect the advantages of the present invention.

[0027] Example 1 is as follows: A method for growing large-size titanium-doped sapphire crystals by a kyberysis method. The thermal insulation structure of the thermal field for crystal growth is composed of a bottom thermal insulation plate 3, an annular thermal insulation tube 2 and an upper thermal insulation plate 1. A carbon felt material with a graphite coating is used. The surface coating roughness is ≤0.1μm, the coating thickness is ≥2mm, and the inner diameter of the annular thermal insulation tube is 610mm (the outer diameter of the crucible is 450mm). The heating structure is composed of a side main heater 4 and a bottom auxiliary heater 5, which are independently controlled to adjust the heating power. The heater is made of hard graphite and has an "S" disk shape. The density of the thermal insulation carbon felt thermal field material is ≥0.15g / cm 3 , the thermal field structure diagram is shown in Figure 2 The crystal growth method is as follows Figure 1 As shown, it mainly includes the following steps: 1) Raw material preparation and loading: according to the doping mass percentage of 0.35%, weigh 420g of titanium dioxide powder with a purity of ≥99.95%, weigh 119.58kg of alumina powder with a purity of ≥99.995%, put them into a mixer, and mix them for 28 hours; put them into a cylindrical mold for isostatic pressing, and then roast them at a roasting temperature of 1820℃ and a roasting time of 10 hours; 75kg of blocks are obtained by striking the titanium-doped alumina sintered ingot, and 45kg of fine materials are obtained by crushing the remaining raw materials; 120kg of raw materials are filled into a molybdenum crucible, and a sapphire seed crystal is installed to complete the furnace; 2) Heating melt: When heating, a mixed gas of Ar and CO is introduced as a protective gas, the CO volume fraction is 5.0%, the gas flow rate is 7L / min, the heating rate is 45-55℃ / h, the melting power is 40.2kW, and the melting time is 35h; 3) Temperature adjustment for seeding: After the raw materials are fully melted, wait for the temperature to rise by 15°C above the full melting temperature to make the melt overheated and cause strong convection, then reduce the power. When the melt surface temperature is 2052.0-2052.4°C, lower the seed crystal to contact the liquid surface for melting and cleaning the impurities and polycrystalline on the lower end of the seed crystal, then reduce the power again to make the liquid surface temperature 2049.0-2049.5°C, and start crystal growth; 4) Crystal growth: Monitor the crystal growth at a growth rate of about 0.3mm / h. When the crystal height reaches 400mm, pull it out of the melt; 5) Crystal cooling in-situ annealing: Increase the CO concentration in the mixed gas, where the CO volume fraction is 10.0%, and the crystal is stopped in place for cooling annealing at a rate of 12.2-14.2℃ / h. When the temperature in the furnace drops to room temperature, the furnace is opened and the crystal is taken out; 6) Wafer H2 annealing: After cutting, a large wafer with a diameter of 308 mm and a thickness of 30 mm without bubble defects was obtained. The processed wafer was subjected to high-temperature H2 annealing with a heating rate of 65-95°C / h, an annealing temperature of 1850°C in a H2 atmosphere, a holding time of 20h, and a cooling rate of 55-80°C / h.

[0028] The titanium-doped sapphire crystal grown in this embodiment weighs 111.35 kg. It is observed by naked eyes that there is no polycrystalline, few crystal bubbles, deep red chroma, small ash content in the furnace reaction, and no impurities attached to the crystal shoulder surface; the dislocation density of the processed wafer is 395 / cm 2 , quality factor value is 175, and uniformity is good.

[0029] Comparative Example 1 is as follows: A process for growing large-size titanium-doped sapphire crystals by the kyberysis method, using a conventional tungsten metal thermal field, the process steps are as follows: 1) Raw material preparation and loading: same as Example 1; 2) Heating melt: When heating, a mixed gas of Ar and CO is introduced as a protective gas, the CO volume fraction is 5.0%, the gas flow rate is 7L / min, the heating rate is 45-55℃ / h, the melting power is 44.6kW, and the melting time is 41h; 3) Temperature adjustment and seeding: same as in Example 1; 4) Crystal growth: same as in Example 1; 5) Crystal cooling and in-situ annealing: same as in Example 1; 6) Wafer H2 annealing: After cutting, a large wafer with a diameter of 152 mm and a thickness of 23 mm without bubble defects was obtained. The annealing process was the same as in Example 1.

[0030] The titanium-doped sapphire crystal grown in this comparative example weighs 112.11 kg. It is observed by naked eye that it is 20% polycrystalline, with many crystal clusters and bubbles, medium red chromaticity, large ash content in the furnace reaction, and impurities attached to the shoulder surface of the crystal. The dislocation density of the processed wafer is 450 / cm 2 , quality factor value 93, poor uniformity.

[0031] In Comparative Example 1, a metal thermal field is used to grow large-sized titanium-doped sapphire crystals by the kyvoiding method. The material chemistry power is higher than that of the graphite thermal field, indicating that the metal thermal field has poor thermal insulation and insufficient thermal stability. The volatile pollution caused by the thermal field reaction is serious, which affects the quality of the crystal. Affected by polycrystalline and crystal cluster bubbles, the diameter of the processed product is less than 200 mm, and the quality factor value is less than 100.

[0032] Comparative Example 2 is as follows: A process for growing large-sized titanium-doped sapphire crystals by the kyberysis method, the thermal field structure used is the same as that of Example 1, and the process steps are as follows: 1) Raw material preparation and loading: same as Example 1; 2) Heating melt: High-purity argon is introduced as protective gas during heating, the gas flow rate is 7L / min, the heating rate is 45-55℃ / h, the melting power is 40.0kW, and the melting time is 33h; 3) Temperature adjustment and seeding: same as in Example 1; 4) Crystal growth: same as in Example 1; 5) Crystal cooling in-situ annealing: Keep the high-purity argon atmosphere unchanged, and keep the crystal in place for annealing at a rate of 12.2-14.2℃ / h. When the temperature in the furnace drops to room temperature, open the furnace and take out the crystal; 6) Wafer H2 annealing: After cutting, a large wafer with a diameter of 184 mm and a thickness of 20 mm without bubble defects was obtained. The annealing process was the same as in Example 1.

[0033] The titanium-doped sapphire crystal grown in this comparative example weighs 111.85 kg. It is observed by naked eyes that there is no polycrystalline, many bubbles penetrate the crystal, the red chroma is medium, the ash content of the furnace reaction is large, and there are impurities attached to the shoulder surface of the crystal. The dislocation density of the processed wafer is 472 / cm 2 , quality factor value 75, poor uniformity.

[0034] Comparative Example 2 uses a graphite hot field, passes high-purity argon, and adopts the cyprophyll method to grow large-sized titanium-doped sapphire crystals. The material power is equivalent to that of Example 1, which shows that the atmosphere in the furnace has little effect on the thermal insulation of the hot field. The volatile pollution caused by the hot field reaction is more serious, which affects the quality of the crystal. Affected by the bubbles penetrating the crystal, the diameter of the processed product is less than 200 mm, and the quality factor value is less than 100.

Claims

1. A method for growing large-sized titanium-doped sapphire crystals by the Kyropoulos method, characterized in that: The thermal insulation structure of the thermal field for crystal growth is composed of a bottom insulation plate, an annular insulation tube and an upper insulation plate, and a carbon felt material with a graphite coating is used. The heating structure is composed of a side main heater and a bottom auxiliary heater, and a graphite material is used. The crystal growth method includes the following steps: 1) Raw material preparation and filling: Titanium dioxide powder and alumina powder are mixed evenly, wherein the mass percentage of titanium dioxide mixed is 0.2-0.6%, and then roasted to obtain titanium-doped alumina sintered ingots, which are crushed and then filled; 2) Heating the melt: A mixed gas of Ar and CO is introduced as a protective gas, wherein the volume fraction of CO is 4.5-7.0% and the rest is Ar, and the temperature is raised to melt the raw materials; 3) Temperature adjustment for seeding: After the raw materials are fully melted, wait for the temperature to continue to rise until it is 10-18°C higher than the full melting temperature of the raw materials. At this time, the melt is overheated and strong convection occurs. Then reduce the heating power to make the melt surface temperature 2048-2053°C, and the descending seed crystal contacts the liquid surface for melting and begins crystal growth; 4) Crystal growth: Control the crystal growth rate to 0.2-0.5 mm / h. When the crystal grows to the required size, pull it out of the melt; 5) Crystal cooling in-situ annealing: Increase the CO concentration in the mixed gas, where the CO volume fraction is 9.5-14.5%, and perform cooling annealing at the same time. After the temperature in the furnace drops to room temperature, take out the crystal, and the crystal diameter is 300-350mm; 6) Wafer H2 annealing: The cut wafer is subjected to high temperature H2 annealing.

2. A method for growing large-sized titanium-doped sapphire crystals by the kyberyzing method as claimed in claim 1, characterized in that: The density of the carbon felt material is ≥0.15g / cm 3 , the roughness of graphite coating is ≤0.1μm, and the coating thickness is ≥2mm; the inner diameter of the annular insulation cylinder is 120-200mm larger than the outer diameter of the crucible; the shape of the graphite heater is "S" disc.

3. The method for growing large-sized titanium-doped sapphire crystals by the kyberyzing method as claimed in claim 1, characterized in that: In the step 1, the mass percentage of titanium dioxide is 0.3-0.5%, the purity of titanium dioxide powder is ≥99.95%, and the purity of aluminum oxide powder is ≥99.995%; the calcination temperature is 1750-1900° C. and maintained for 5-15 hours.

4. A method for growing large-sized titanium-doped sapphire crystals by the kyberyzing method as claimed in claim 1, characterized in that: In the step 2, in the mixed gas of Ar and CO, the volume fraction of CO is 5-6.5%, and the gas flow rate is 5-8 L / min.

5. The method for growing large-sized titanium-doped sapphire crystals by the kyberyzing method as claimed in claim 1, characterized in that: In the step 3, after the raw materials are fully melted, the temperature is allowed to continue to rise until it is 12-16°C higher than the fully melted temperature of the raw materials. At this time, the melt is overheated and strong convection occurs, so that the raw materials form a uniformly distributed melt. The heating power is then reduced. When the melt surface temperature is 2051.8-2052.8°C, the seed crystal is lowered to contact the liquid surface for melting and cleaning the impurities and polycrystalline on the lower end surface of the seed crystal. The heating power is then reduced. When the melt surface temperature reaches 2048.2-2050.2°C, crystal growth begins. The seed crystal is a sapphire seed crystal or a titanium-doped sapphire seed crystal.

6. A method for growing large-sized titanium-doped sapphire crystals by kyberysis as claimed in claim 1, characterized in that: In step 4, the crystal growth rate is 0.25-0.45 mm / h.

7. The method for growing large-sized titanium-doped sapphire crystals by the kyberyzing method as claimed in claim 1, characterized in that: In step 5, the CO concentration in the mixed gas is increased, wherein the CO volume fraction is 10.0-12.0%.

8. The method for growing large-sized titanium-doped sapphire crystals by the kyberyzing method as claimed in claim 1, characterized in that: In the step 5, the temperature is lowered and annealed at a rate of 11.2-16.2° C. / h.

9. The method for growing large-sized titanium-doped sapphire crystals by the kyberyzing method as claimed in claim 1, characterized in that: In step 6, the cut wafer is subjected to high temperature H2 annealing, with a heating rate of 55-185°C / h, an annealing temperature of 1800-1900°C, a holding time of 10-50h, and a cooling rate of 45-135°C / h.

Citation Information

Patent Citations

  • Sapphire single crystal growth method

    CN112501690A

  • Nano patterned sapphire substrate and preparation method and application thereof

    CN114695072A

  • Doped sapphire growth method using main heater and auxiliary heater

    CN118186573A

  • Device for growing high-quality and large-size titanium doped sapphire crystal

    CN204265891U

  • Manufacturing a titanium sapphire laser crystal using a mixture of carbon monoxide and an inert gas

    DE102005043398A1